A variação dos pronomes tu/você no português falado em Luanda (Angola) - Santos, Higor Teixeira dos (2026)
Angola is an African country composed of peoples who speak more than twenty languages, of which Portuguese stands out as the only official language (Art. 19) of the Constitution of the Republic (2010). Portuguese is a more prestigious language since it is used in bureaucratic documentation, justice, education, and formal communication by the State. Portuguese arrived in Angola through colonization and today is a variety with its own characteristics that carry Angola's unique identity. The uses of the pronouns tu/você vary from variety to variety depending on the “standardization” applicable in each variety, hence the question: how are second-person singular pronouns used in the Angolan variety of Portuguese? This study seeks to examine the pronoun forms tu/você in the Portuguese of Luanda in order to understand the variation in sociolinguistic reality. In addition, it describes these pronoun forms based on interviews through a study in apparent time and discusses the socio-historical reasons for their use, taking into account the interference of local languages. The research stems from an attempt to establish a meaningful study on Angolan Portuguese, contributing to its socio-historicalcultural aspects, resulting in projections for scientific research and stimulating future research in this field. Following its relevance, which is to provide a current overview of the forms of address existing in Angolan territory (the most used and the less used), describing emerging expressions that are not part of the forms of address considered classic, influenced by social stratum. DID (Dialogue between Informant and Documenter) interviews will be used for analysis, stratified by age group, gender, education, mother tongue, and place of birth of the informant. The corpus to be used in this study consists of a sample of vernacular speech from the city of Luanda, the capital and largest urban center of Angola, and belongs to the database of the project “In search of the roots of Brazilian Portuguese.” The corpora consist of two types of speech samples, one from speakers of Portuguese as their mother tongue, totaling 32 interviews, and the other from speakers who have Portuguese as a second language, consisting of 24 interviews. Therefore, in the research project described here, 56 interviews will be used, all of which have already been transcribed. The research was submitted to the Research Ethics Committee (CEP/UEFS), with favorable opinion number 7,109,599 and Certificate of Presentation for Ethical Review - CAAE: 83267824.6.0000.0053. The investigation was conducted using the theoretical and methodological assumptions of the theory of linguistic variation and change (Weinreich; Labov; Herzog, 2006 [1968]; Labov (2008 [1972]) of variationist sociolinguistics. Research on the phenomenon under study shows that tu is increasingly less used by Angolan speakers, especially uneducated informants, who prefer the use of você, which is increasingly productive and used by both educated and uneducated speakers. Therefore, this research demonstrates the preference for você in practically all variables, revealing explanations of a linguistic and social nature. The internal variable verbal agreement proved to be one of the categories in which você had the highest percentages in relation to non-agreement (você, 93.9%; tu, 6.1%). The age variable proved to be one of the most representative when it comes to social variables, with very high results for você in the young (71.4%), middle-aged (91.9%), and elderly (84.5%) age groups. In general, there was a tendency to favor the pronoun você in certain social and discursive contexts, which points to a possible expansion of this form in the Portuguese spoken in Luanda. The pronoun tu, on the other hand, was restricted to specific contexts, such as the subject filling variable.